Intervenciòn de enfermería en ulceras varicosas para prevenir amputaciones de miembros inferiores - Enriquez Zambrano, Jenniffer Melissa; Romero Romero, Milena Jamileth (Machala : Universidad Técnica de Machala, 2022)
Venous ulcers are considered as lesions or losses of skin substances produced by the malfunction of blood circulation either through veins or arteries, mainly affecting the lower limbs, decreasing their physical mobility, in our country it is considered one of the main high-risk diseases occupying between 80 and 90%, the people who are more likely to suffer from this disease are those with type 2 diabetes mellitus.We must know that there are no visible signs and symptoms in the early term as soon as a venous ulcer is going to develop, but we can diagnose it when there is the presence of heaviness in the legs and itching that causes itching in the area where it is going to develop and in turn considering his history of deep vein thrombosis or the presence of varicose veins as a triggering cause. The treatment begins from the moment the patient goes to the vascular surgery specialist, to carry out an arterial study. The objective of this case study is to apply the nursing care process, to reduce the risks of the patient, avoiding the worsening of the wound or its development in another area, as well as avoiding the amputation of their lower limbs, based on the theory of Dorothea Orem self-care. The methodology applied in this study is analytical, qualitative and descriptive.The problem we identified is a 68-year-old female patient, a resident of the Forest 1 site belonging to the Santa Rosa canton, who attended the health center of a certain town on June 22, 2022, reporting a history of varicose ulcers, with presence of general malaise, area affected by ulcers reddened and with the presence of purulent fluid, approximately in a time range of 1-month, Personal History: varicose ulcers and type 2 diabetes mellitus. Family History: Brother and parents with type 2 diabetes mellitus. Physical Exam: Blood Pressure: 130/80, Heart Rate: 78x', Respiratory Rate: 22X', Temperature: 36. 5º, Oxygen Saturation: 97%, Weight:55.8KG, Height: 151cm, Skin and mucosa with presence Jaundice, Ventilated lungs, Extremities with diminished muscle tone and strength, Neurological: Patient oriented in time, space and person.
Las úlceras venosas son consideradas como lesiones o pérdidas de sustancias cutáneas producidas por el mal funcionamiento de la circulación sanguínea ya sea por venas o arterias, afectando principalmente los miembros inferiores y disminuyendo la movilidad física de los mismos, en nuestro país es considerado como una de las principales enfermedades de alto riesgo ocupando entre el 80 y 90%. El presente estudio de caso tiene como objetivo aplicar el proceso de atención de enfermería, para aminorar los riesgos del paciente evitando complicaciones en la herida o que se desarrolle en otra zona, y evitar a su vez la amputación de sus miembros inferiores, basado en la teoría del autocuidado de Dorothea Orem. La metodología que se aplicó en este estudio es de aspecto analítico, cualitativo y descriptivo. La problemática que identificamos es de un paciente de 68 años de edad de sexo femenino, residente del sitio el Bosque 1 perteneciente al cantón Santa Rosa, acude al centro de salud de cierta localidad el 22 de junio del 2022 refiriendo antecedentes de úlceras varicosas, con presencia de malestar general, zona afectada por úlceras enrojecida y con presencia de líquido purulento, aproximadamente en un rango de tiempo de 1 mes, Antecedentes Personales: úlceras varicosas y diabetes mellitus tipo 2. Antecedentes Familiares: Hermano y padres con diabetes Mellitus tipo 2. Exámen Físico: Tensión Arterial: 130/80, Frecuencia Cardiaca: 78x’, Frecuencia Respiratoria: 22X’, Temperatura: 36, 5º, Saturación de Oxígeno: 97%, Peso:55,8KG, Talla: 151cm, Piel y mucosas con presencia de Ictericia, Pulmones ventilados, Extremidades con tono y fuerza muscular disminuida, Neurológico: Paciente orientada en tiempo, espacio y persona.
Keywords: ULCERAS VARICOSAS; PROCESO DE ATENCION DE ENFERMERIA; DIAGNOSTICO